Evolución histórica de los delitos contra el deber de presencia en el Derecho Histórico Militar: Desde el Constitucionalismo decimonónico hasta nuestros días - Martín Delpón, José Luis (Cuadernos de Historia del Derecho, 2007)
From the Roman law to the present time, the desertion has been considered an obvious example of military crime. The present article tries to provide a global vision of the evolution of this military crime throughout the 19th century constitutionalism and its consolidation in our legal system, already in the 20th century, both at the Code of Military Justice of 1945 as at the Military Penal Code, approved by Statutory law 13/1985, as well as the perspective of its permanence in our legal system in accordance with the new challenges of the national defense and their incidence in the military law.
Keywords: Desertion; Service neglect; Military law; Military justice